(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: This study aimed to assess knowledge, attitude, usage and factors affecting dietary herbal supplements’ usage pattern among chronic disease patients. Materials and Methods: A cross-sectional study was conducted among patients with chronic diseases. This study was conducted using a pre-validated, self-administered questionnaire, designed after an extensive literature review. Results and Discussion: Out of total 134 patients, 120 (89.6%) were males while 14 (10.4%) were females. Our studied patients had very good knowledge about dietary herbal supplements usage (mean knowledge score 7.8 (±3.45)) and majority had relatively positive attitude 103 (76.9%) toward dietary herbal supplements usage. This study found a strong positive correlation between the knowledge and attitude scores (r = 0.903, P = 0.011). Elderly, males, high-income and patients suffering from comorbidities had higher knowledge and positive attitude scores compared to the rest (P < 0.05). The study’s findings showed that the majority of the patients with chronic illnesses used ginger 41 (13.1%), mint 35 (11.2%), fennel 34 (10.9%), and anise 34 (10.5%) as dietary herbal supplements. Conclusion: The good knowledge and moderate to strong attitude toward dietary herbal supplements still emphasized the role of healthcare providers especially clinical and hospital pharmacists to increase awareness about the benefits of dietary herbal supplements among the chronic disease patients suffering from multiple comorbidities.